Institutionalism and intergovernmental cooperation: a discussion about public consortia and the jurisdiction conflict in brazilian public services - Cattani, Yan Nonato (2023)
Since the enactment of the 1988 Constitution, the Brazilian public services have suffered from several clashes in public services derived from its complex federalist system. To operationalize these services, this system oscillates between moments of cooperation and competition among the federative entities, that is, among the federal, state, and local governments, acting in jurisdictional conflicts. As local governments in Brazil are responsible for service provision in all types of public services, in 2005 the Federal Government enacted the "Public Consortia" law to ease such conflicts, creating a specific Cooperative Intergovernmental Arrangement (CIA), conferring legal stability to municipalities to promote cooperation among all federative entities. Within this context, this thesis sheds light on how intergovernmental cooperation provided by public consortia can reduce jurisdictional conflicts and improve the performance delivery of public services in Brazil. We addressed this thesis' question through a three-study based on an approach of mixed methods. The first study analyzed 104 studies seeking to evaluate Brazilian CIA performance through an integrative review using snowballing and statistical bibliography techniques. As a result, we unveil that qualitative studies improve the assertiveness of quantitative studies, and panel methods can be considered a recent trend to quantitatively evaluating the public policies delivered by CIA. The second performed a comparative study to verify the international strategy across countries, between a unitary state (France) with relatively more mature cooperative intergovernmental arrangements (CIA) and a federalist state (Brazil) with a developing CIA stage. The comparative analysis relies on the Institutional approach and performed in-depth interviews to understand the practical meaning of performance stressing public managers' points of view. Results have shown that the institutional development of CIA and their jurisdictional attributions differ between countries, since there is a duality between local autonomy and the sectoral limitation of the scope of services provided by CIA. To verify the findings of the second study, in the third study we chose a relatively developed sector (solid waste management) with available information to estimate the impact of the gradual implementation of solid waste public consortia services from 2005 to 2019. Using the panel method of difference in differences (DiD) and a more robust approach, the staggered DiD, we estimated the impact of such services on the health and public expenditure indicators. As a result, we obtained robust econometric findings, uniting a state-of-the-art econometric method with the guidelines of Institutional Cooperation Theory, showing that the participation of public consortia in the provision of solid waste services in Brazilian municipalities is relevant for improving some health outcomes and reducing expenses in the environmental budget. To conclude, the thesis shows that while sectoral attributions for public services are not a reality in Brazil, cooperation among governments should be fostered to reduce jurisdictional conflicts. The CIA is a viable option to promote the coordination and development of public policies in Brazil.